The Social and Academic Scene in Chetan Bhagat’s Novels: Analyzing Corruption and Stress in Chetan Bhagat's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Literature influences and is influenced by society. The novel form is closer to life than any other literary form. In his novels, Chetan Bhagat emerges as a keen observer of the present-day social and academic scene in India. In his fictional world Indian education system suffers from two diseases, namely stress and corruption. Stress takes a heavy toll primarily on the students who, under intense parents-teacher-peer pressure, prepare for board exams or a ruthlessly competitive entrance test, or are enrolled in some professional course. On daily basis we read reports in leading newspapers about the presence of corruption in the field of education as well as the impact of neck-breaking competition for admission and jobs. The stress factor hits hard, especially the students who are enrolled in professional courses because the stakes there are very high. They find it very hard to cope with the rising academic expectations and quite a few of them fall prey to their own and the parents’ unrealistic expectations. This paper tries to analyze some novels written by Chetan Bhagat in which he takes up the issues of corruption and stress prevalent in the academic world in India.